2023
DOI: 10.3390/ph16020219
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Endostatin as a Potential Radiosensitizer in the Treatment of Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is the most prevalent type of lung cancer, which is the leading cause of cancer-related deaths worldwide. Over the past decades, tumour angiogenesis has been intensely studied in the treatment of NSCLC due to its fundamental role in cancer progression. Several anti-angiogenic drugs, such as recombinant endostatin (RE), have been evaluated in several preclinical and clinical trials, with mixed and often disappointing results. However, there is currently an emerging interest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 181 publications
0
1
0
Order By: Relevance
“…Increasing evidence has demonstrated that Endostar (Endo) often causes severe multiorgan injury, particularly cardiac trauma. Since Endo-rDFN could reduce the biodistribution and direct exposure of Endo to normal tissues, we investigated whether Endo-rDFN could mitigate Endo-induced multiorgan injury. To evaluate the long-term safety of Endo-rDFN, we conducted a series of experiments, including cardiac function assessment, histopathological analysis, and hematological and biochemical assays.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence has demonstrated that Endostar (Endo) often causes severe multiorgan injury, particularly cardiac trauma. Since Endo-rDFN could reduce the biodistribution and direct exposure of Endo to normal tissues, we investigated whether Endo-rDFN could mitigate Endo-induced multiorgan injury. To evaluate the long-term safety of Endo-rDFN, we conducted a series of experiments, including cardiac function assessment, histopathological analysis, and hematological and biochemical assays.…”
Section: Resultsmentioning
confidence: 99%